Penerapan Green Accounting untuk Pengelolaan Limbah pada Peternakan Sinatria Farm Yogyakarta Periode 2023 - Yeyen Mutia Ramadhany (Syntax Idea, 2052)
The research aims to determine the application and suitability of the disclosure and presentation of Green Accounting financial reports on the Sinatria Farm Yogyakarta farm with PSAK No.1. The type of field research research with the method used is qualitative, namely research that does not use numbers or statistical calculations, but provides descriptive results for the research. The research location was at Sinatria Farm, which is located in Sleman Regency, Yogyakarta Special Region, with two resource persons, namely employees who were directly related to the variables studied. Data collection uses primary data from observations and interviews with respondents based on research problems, as well as secondary data in the form of general data and livestock financial records. The data analysis method uses 3 stages of qualitative data analysis according to Miles and Huberman, namely data reduction, data presentation, and drawing conclusions. The results of the research state that the implementation of Green Accounting carried out by Sinatria Farm Yogyakarta has been carried out well in its waste management, the disclosure and presentation of Green Accounting financial reports at Sinatria Farm Yogyakarta is not in accordance with PSAK No.1, but still uses financial reporting notes according to the needs of the farm using language that is easy for the livestock to understand. In this regard, steps that must be taken are to look for other innovations related to contributions to the environment, and start determining environmental costs in Green Accounting, which records financial reporting in accordance with PSAK No.1.